P‐glycoprotein and chronic rhinosinusitis. Issue 3 (1st September 2018) - Miyake, Marcel M.; Nocera, Angela; Miyake, Michelle M.
Abstract : Chronic rhinosinusitis (CRS) is a heterogeneous definition that includes different disease states that usually are associated with abnormal inflammatory responses. Besides being prevalent, the mechanisms involved in its pathogenesis are not clear and there are few therapeutic options with tolerable side effects. P‐glycoprotein (P‐gp) is an efflux pump responsible of extruding xenobiotics and cellular metabolites from multiple cell types. It has been widely studied in the cancer field, due to its ability to confer resistance to chemotherapy. It also promotes Type 2 helper T‐cell polarizing cytokine secretion in CRS and may represent a potential target to differentiate subtypes of CRS and personalize treatment. This state‐of‐the‐art review explores current knowledge on the participation of P‐gp in the pathogenesis of CRS, the P‐gp inhibition as a novel targeted therapeutic strategy and the exosomal P‐gp test, a non‐invasive biomarker that can represent an important advance in the field of rhinology.